Calorimetric analysis of Portevin-Le Chatelier bands under equibiaxial loading conditions in Al–Mg alloys: Kinematics and mechanical dissipation. (February 2017) - Le Cam, Jean-Benoît; Robin, Eric; Leotoing, Lionel; Guines, Dominique
Highlights: The calorimetric analysis of PLC bands is carried out under equibiaxial loading. The kinematics of PLC bands is investigated from the calorimetric response. The mechanical dissipation due to PLC band initiation and propagation is mapped. Graphical abstract: Abstract: This paper investigates the thermomechanical behavior of Al–Mg alloys submitted to equibiaxial loading until failure. More particularly, the study aims to characterize calorimetric signature accompanying the formation and propagation of Portevin-Le Chatelier (PLC) bands induced by such a loading condition. Digital Image Correlation (DIC) and infrared thermography (IRT) on both sides of a cruciform shaped specimen were performed in order to characterize full kinematic and thermal fields on the specimen surface. Heat source field was reconstructed from the temperature field and the heat diffusion equation. The heat source map enables us to visualize spatio-temporal gradients in the calorimetric response of the material and to investigate the kinematics of PLC bands induced by equibiaxial tensile loading. At the specimen center, the heat source exhibits jumps that fit with jumps of temperature and equivalent deformation rate. Until a 30% equivalent strain rate is reached, these jumps are due to repeatable PLC band propagation in the two perpendicular loading directions. In certain cases, heat source maps may be seen as mechanical dissipation maps.